Understanding the rise of augmented reality–based apps post-Pokémon GO. Issue 3 (1st November 2018) - Nath, Samrat
Augmented reality (AR) platforms integrate virtual ambience with the real-life environment of a user. One of the recent innovative usages of AR was Pokémon GO app, which was a stupendous success owing to its huge user base and the convenient usage of technology. This article attempts to understand the proliferation of AR-enabled apps post-Pokémon GO using content analysis. The study uses primary data from the Google Play Store (Android) and the App Store (iOS) (Indian versions) to inductively infer the current market trends. In conclusion, the article looks at the plausible functions of the platform as a media channel.